International labor migration and remittances: Towards development-friendly migration policies - Aslıhan Arslan; Alexandra Effenberger; Matthias Lücke; Toman Omar Mahmoud (The crisis and beyond, 2009)
Risk evaluation is crucial for practitioners as it allows them to make better investment decisions. However, the recently witnessed financial turmoil has demonstrated the inadequacy of many models for preventive risk evaluation. In particular, it is now evident that new methods are needed to anticipate and manage risk in asset markets more accurately. In this article we discuss some of the "blind spots" in risk management uncovered by the financial crisis and suggest alternative models for the evaluation and prevention of risk that can be useful for the new "toolkit" of financial practitioners and regulators.
Keywords: 330; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Entwicklung; Wirtschaftskrise; Migrationspolitik